PRELIMINARY ESTIMATES OF BUILDING COST AND THE LOWEST EVALUATED TENDER - Eliufoo, Harriet K (Tanzania Journal of Engineering and Technology, 2018)
The paper has investigated and established to what extent are preliminary estimates of building costs close to the lowest evaluated tender and how geographical proximity influences the variance between preliminary estimate and the lowest evaluated tender. A multiple case study constituting 43 building projects in Tanzania were statistically analysed covering a period from 1995- 1999. Findings reveal a significant variance exists between the quantity surveyor ' s preliminary estimate figure and the lowest evaluated tender; and that the variance between the quantity surveyor ' s figure and the bidder is small when the proposed building project is geographically closer to the quantity surveyor ' s base. Analysis of variance (one - way) has shown geographical distance has a statistical significance on the variance between the preliminary estimates and the lowest evaluated tender. The study has established that the object of preliminary estimates in building costs, that of making the client aware of his financial obligations at early stages of a building project are not met fully.